THE FACTORS AFFECTING UNIVERSITY PROFESSORS’ HEALTH AND WAYS OF ITS IMPROVEMENT - N. V. Polunina; L. S. Soltamakova (Сеченовский вестник)
The article analyses the professional activity of univesity professors and the occupational hazards, including emotional burnout. The study found that despite higher incidence, revealed in medical examinations, 25.8% of professors do not underwent annual medical examination and 56.7% of professors do not follow the medical recommendation. 78,6% of teachers called lack of a special health care facility for university faculty members and students. The incidence structure is dominated by respiratory deseases, including acute respiratory diseases, laryngitis and laryngotracheitis, followed by professional burnout. The analysis of risk factors revealed occupational hazards as the main cause of poor health status of university professors. The most signiﬁcant are unsatisfactory wages and the necessity of a additional part-time position, need of existence of the second work, prolonged ﬁxed position, high psychological pressure and working weelk longer than 36 hour. Taking into the consideration the creative nature of educational and research activities and prolonged working week we recommend to optimize research and out-of-class activities and limit the faculty obligatory presence by the instruction hours. We recommend to set up specialized health care centers for faculty and students for regular checkups and reabilitation.